Khaṣā’iṣ al-Mustawá al-Ṣarfī li-Lahjat al-‘Arabīyah al-Nījīrīyah - Alqali, Musa Kalim; Saleh Muhammad Kabir (Al-Ma‘rifah, 2019)
The Arab tribes locally known as Shuwa Arabs represent a segment of Nigerian society. They came from the Arabian Peninsula for varied aims. And they spoke an Arabic dialect which conforms or differs from other ancient or modern Arabic dialects in many traits which they inherit from their forefathers, which shows that they preserve their Arabic Identity. Although this dialect is strictly following Arabic morphology. But at times they have their unique morphology perhaps it can be traced to some ancient Arabic dialects. Morphology has gained great importance because it helps to understand the meaning of phrases and words through usage. To fathom this fact in the Nigerian Arabic dialects, the researcher tries to tackle this topic by studying the morphological issues which may help to reach what he wants.